2020
DOI: 10.1002/psp.2403
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in self‐assessed health in Scotland: The role of socio‐economic status and migrant generation

Abstract: This study investigates ethnic differences in self‐assessed health in Scotland and their determinants, focusing on socio‐economic status and migrant generations. We use the Scottish Health and Ethnicity Linkage Study (SHELS) and apply regression analysis to data for 4.6 million people. The analysis shows that the White British, Other White and Chinese groups reported better health than the White Scottish population, whereas Pakistani and Indian populations had worse health outcomes. For the latter two groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 82 publications
(151 reference statements)
1
23
0
Order By: Relevance
“…The poorer mental well-being observed among the Pakistani/Bangladeshi, other ethnicities group, and non-UK born individuals could be related to the socio-economic and lifestyle differences or to place-related contextual differences. Literature on ethnic inequalities in health has shown that ethnic minorities often live in more disadvantaged communities, and have lower socio-economic status, lower healthcare coverage and higher job/income insecurity [ 34 , 73 , 74 ], which increases their risk of physical and mental illness. Nevertheless, our analysis adjusted for the main socio-economic and lifestyle factors of individuals including age, gender, marital status, education, occupation, financial situation, and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The poorer mental well-being observed among the Pakistani/Bangladeshi, other ethnicities group, and non-UK born individuals could be related to the socio-economic and lifestyle differences or to place-related contextual differences. Literature on ethnic inequalities in health has shown that ethnic minorities often live in more disadvantaged communities, and have lower socio-economic status, lower healthcare coverage and higher job/income insecurity [ 34 , 73 , 74 ], which increases their risk of physical and mental illness. Nevertheless, our analysis adjusted for the main socio-economic and lifestyle factors of individuals including age, gender, marital status, education, occupation, financial situation, and cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality from all causes was also shown to be lower for immigrants in England and Wales (Wallace & Kulu, 2015). This could be explained by the "healthy migrant effect": immigrants who leave their countries of origin tend to be healthier than those who stay in the country of origin and the population in the destination country (Cézard et al, 2020;Wallace & Kulu, 2014). Yet over time, immigrants assimilate to the culture and living habits of the destination country, a process named as "acculturation", gradually exhibiting health behaviours related to their diet, smoking, and alcohol consumption similar to that of the native population (Abraído-Lanza et al, 2005).…”
Section: Mechanisms Underlying Ethnic Inequalities In Health In the C...mentioning
confidence: 99%
“…Many studies show that ethnic minorities have poor health due to the fact that they live in more disadvantaged communities and have lower socio-economic status as well as poor housing conditions and healthcare coverage as compared to the majority of population (Egede, 2006;Pearce et al, 2006;Su et al, 2011). In the UK, the poorest health is often reported by Bangladeshi and Pakistani ethnic groups, followed by Caribbeans and Indians (Cézard et al, 2020;Nazroo, 2003). However, when socioeconomic factors such as educational attainment, occupation, social class, income, and household tenure, are controlled for these observed differences by ethnic groups are significantly reduced (Cézard et al, 2020;Evandrou et al, 2016).…”
Section: Mechanisms Underlying Ethnic Inequalities In Health In the C...mentioning
confidence: 99%
See 1 more Smart Citation
“…In neighbouring Scotland,Cézard et al (2020) investigate the selfreported health of migrants and their descendants, where it has long been recognised that immigrants experience substantial health and SES advantages over the native population. They use individual-level data from a unique data source-the Scottish Health and Ethnicity Linkage Study (SHELS) study, which links data for all Scottish 2001 Census respondents (4.6 million people, 94% of the whole population) with hospitalisation and mortality records.…”
mentioning
confidence: 99%